(untitled) - Benninga, Simon Z. (New York, 1997)
The book provides an integrated, comprehensive method of valuing assets, firms, and securities. It begins with a review of the financial and accounting techniques needed for the implementation of a full valuation, proceeds with a detailed discussion of the valuation process, leading the reader from the very first steps of building pro-froma financial statements, through the translation of these projections to values, to the division of firm value among the different security holders of the frim: shareholders, debt holders, and conversible security holders.
Keywords: Corporations,Corporations; Finance,Valuation